Electron Donor Acceptor Complexes and Copolymerization Behavior of Oxazole and Thiazole with Maleic Anhydride. A Comparison with Other Five-Membered Heterocyclic Donors - A. Ragab, Yousif; B. Butler, George (Gezira Journal of Engineering and Applied Sciences, 2014)
The electron donor-acceptor (EDA) complexes of oxazole (OX) and thiazole (THZ) with maleic anhydride (MAH) were detected and characterized. Radical copolymerization of OX-MAH gave nearly an alternating copolymer, while THZ-MAH gave mainly poly (MAH). EDA complexation parameters and copolymerization reactivities of MAH with various one and two heteroatom five-membered heterocycles were compared and correlated with the physicochemical properties of the heterocycles. Polymerization behavior seemed to be determined by EDA complexation, aromaticity, activity, and basicity of the heterocycle.